Factors Influencing Brand Loyalty Towards Sportswear in Bandung - Wijaya, Renaldo; Aprianingsih, Atik (Journal of Business and Management, 2015)
Abstract. Sportswear has been accepted by millions of people in Indonesia. In the recent years, the usage of sportswear in Indonesia became more and more acceptable, and we could see them in the malls, the roads, the schools and places, especially in Bandung. Many people became loyal to sportswear brands, and we could see that from what they wore. Sportswear including sports jacket, footwear, shorts, caps and many other types of apparel is very common nowadays because many people have been wearing them for quite some time.This research is made with the objective of learning what makes a customer loyal toward a sportswear brand, and to see whether the factors are significant or not. The researcher believe that local or any international sportswear brands could learn from the worldwide leading sportswear brands, such as Nike and Adidas, and build brand loyalty for the customers with the same quality as the best sportswear.The researcher believe if many sportswear brand could learn from the factors influencing brand loyalty towards sportswear in Bandung, any sportswear brand could build the brand loyalty in big cities such as Jakarta, and Surabaya, as Bandung is known as ‘The City of Mode’. This research will separate the 7 main factors building the brand loyalty toward a sportswear brands, such as Product Quality (PQ), Style (ST), Brand Name (BN), Store Environment (SE), Service Quality (SQ), Sales Promotion (SP), Price (PR) with the Brand Loyalty (BL) itself. With the Questionnaire of 39 questions, the quantitative data was filled by Young-Adults in Bandung to see the priorities in the brand Loyalty. After the Questionnaire is filled with respondents, the researcher use the SPSS 22 to do the reliability and validity test, calculate and descriptively analyze the the response and use regression to see the correlation of the factors with brand loyalty. All the hypothesis used in this research supports the current hypothesis and support the work of previous researchers, such as Yee and Sidek (2008), and Lau & Lee (1999). Thus research from both practical and theoretical aspect is discussed to build brand loyalty as well as consideration for future research. Keyrords: Marketing, Brand Loyalty, Sportswear, Product Quality, Store Environment, Service Quality, Pricing, Promotion, Brand Name